Analisis pengaruh penggunaan e-commerce, media sosial dan sosial media marketing terhadap pendapatan usaha mikro kecil menengah (UMKM) fashion di Kota Jambi - Permata Ayunda, Kharina; Achmad, Erni; Emilia, Emilia (e-Journal Perdagangan Industri dan Moneter, 2023)
In the digital era of fintech 4.0 and the industrial revolution, it is now an opportunity for MSMEs to advance their own businesses. Digital progress and MSMEs have a close relationship because nowadays technology has become a factor in increasing income for MSMEs. The technology that is often used by MSMEs includes e-commerce, social media and marketing through social media marketing. This type of research uses quantitative and also uses descriptive approach. This study relies on primary and secondary data and uses the Slovin formula to determine the sample. The data analysis method in this research uses a logistic regression model. Based on the research and data processing results that have been carried out, it can be seen that the variables e-commerce, social media and social media marketing have a significant influence and results on the income of Fashion MSMEs in Jambi City. With this research, it is hoped that Fashion MSME players in Jambi City and all other MSMEs who have not used and are not very active in using e-commerce, social media and social media marketing will start using and actively use them, in order to increase the income of Fashion MSMEs.